Repositioning Artificial Intelligence in Value-Based Islamic Religious Education - Ellisa Fitri Tanjung; Nurman Ginting; Nursakinah Nasution (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly influenced educational transformation, including within Islamic Religious Education (Pendidikan Agama Islam/PAI). This study aims to systematically examine the empirical and conceptual evidence regarding the implementation of AI-based digital learning in strengthening students’ understanding of Islamic values, particularly among Generation Z learners in Muhammadiyah senior high schools. Using a Systematic Literature Review (SLR) approach guided by Kitchenham and Charters (2007) and the PRISMA framework, 28 peer-reviewed articles published between 2019 and 2025 were analysed from the Scopus, Web of Science, Dimensions, and Google Scholar databases. The findings indicate that AI applications such as adaptive learning systems, generative chatbots (e.g., ChatGPT), AI-based multimedia, and augmented reality significantly improve cognitive learning outcomes, student engagement, and critical thinking skills. However, the majority of studies emphasise measurable academic performance, while ethical considerations, theological validation, and character formation remain underexplored. This imbalance reveals a conceptual gap between technological efficiency and the holistic objectives of Islamic education. The study concludes that AI integration in PAI must be repositioned as a value-sensitive pedagogical instrument rather than merely a cognitive enhancement tool. Effective implementation requires ethical supervision, interpretative guidance, and alignment with Islamic educational philosophy to ensure balanced intellectual, moral, and spiritual development in the digital era.